Ukraine : Technical Assistance Report-Self-Funding of the National Securities and Stock Market Commission. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the self-funding model of the National Securities and Stock Market Commission (NSSMC) in Ukraine. There are a number of challenges with NSSMC's funding and the constraints placed on it through the Ukrainian government budget process. The analysis conducted by the NSSMC and reviewed by the mission confirms the general benefits of moving to a self-funding model for the NSSMC. The legislative measures should be complemented by improvements in the NSSMC systems and processes. Self-funding of securities and other financial services regulators is increasingly becoming the international norm. The trend to self-funding is even more pronounced within Europe.